The Primal Elements : Empedocles and Buddhist Philosophy: The Primal Elements : Empedocles and Buddhist Philosophy - (Prapin), PhramahaParamet Paramissaro; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article aims to present the first elements in the viewpoint of Empedocles and Buddhist philosophy. It is found that the first elements in the view of the Empedocles refer to the 4 elements, which are soil, water, air, and fire, which are not constant. broken and the essence of the world The world arises from the merging of the first elemental element in the Buddhist philosophy, meaning the five aggregates, namely form, feeling, contraction, sankhara, and spirit. that come together to make things It is not permanently fixed, it follows the trilak law, i.e.Anacchan, Dukkha, Anatta